2022
DOI: 10.1093/mnras/stac289
|View full text |Cite
|
Sign up to set email alerts
|

Updated modelling and refined absolute parameters of the oscillating eclipsing binary AS Eri

Abstract: We present a new study of the Algol-type eclipsing binary system AS Eri based on the combination of the MOST and TESS light curves and a collection of very precise radial velocities obtained with the spectrographs HERMES operating at the Mercator telescope, La Palma, and TCES operating at the Alfred Jensch telescope, Tautenburg. The primary component is an A3 V-type pulsating, mass-accreting star. We fitted the light and velocity data with the package PHOEBE, and determined the best-fitting model adopting the … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…The primary star of J0247-25 is exactly synchronized, with a rotation-to-orbit frequency ratio f rot /f orb = -+ 1.00 0.01 0.02 . But the mass-gaining primary component of AB Cas rotates slightly faster than the orbital speed, f rot /f orb = -+ 1.11 0.02 0.01 , probably accelerated by the impact of the gas stream from the secondary donor (Lampens et al 2022). Conversely, the rotation rate of the OO Dra primary is lower than the synchronous value, f rot /f orb = 0.78 ± 0.01.…”
Section: Binary Evolution and Synchronization In Close Binary Systemsmentioning
confidence: 89%
See 1 more Smart Citation
“…The primary star of J0247-25 is exactly synchronized, with a rotation-to-orbit frequency ratio f rot /f orb = -+ 1.00 0.01 0.02 . But the mass-gaining primary component of AB Cas rotates slightly faster than the orbital speed, f rot /f orb = -+ 1.11 0.02 0.01 , probably accelerated by the impact of the gas stream from the secondary donor (Lampens et al 2022). Conversely, the rotation rate of the OO Dra primary is lower than the synchronous value, f rot /f orb = 0.78 ± 0.01.…”
Section: Binary Evolution and Synchronization In Close Binary Systemsmentioning
confidence: 89%
“…Another example is the semidetached Algol, AS Eri. Lampens et al (2022) obtained a synchronicity parameter of F 1 = 1.1-1.2 and concluded that the primary star rotates supersynchronously. This agrees well with the result of the rotational velocity that the observed v i sin 1 = 36 ± 3 km s −1 found by Glazunova et al (2008) is a little larger than the predicted v 1,sync = 32.9 ± 0.1 km s −1 , adopting a radius of 1.733 ± 0.006 R e , obtained by Lampens et al (2022).…”
Section: Binary Evolution and Synchronization In Close Binary Systemsmentioning
confidence: 98%
“…Ribas et al 2000;Torres et al 2010). Thus, these targets are critical to uncovering the physical phenomena of massive pulsating stars in EBs (Lampens et al 2022;Tkachenko et al 2020;Johnston 2021;Southworth & Bowman 2022;Simón-Díaz et al 2017).…”
Section: Introductionmentioning
confidence: 99%
“…The study of EBs with 𝛿 Sct components can provide accurate asteroseismic models which are linked to the short-term stellar evo-★ E-mail: burak.ulas@comu.edu.tr lution dynamic because they undergo a series of several physical phenomena such as tidal interactions between the components, mass transfer stages and pulsations (Samadi Ghadim et al 2018;Lampens 2021;Lampens et al 2022). Particularly, in close binary systems, tidally-excited non-radial pulsations can also be involved in the stellar evolution process (Aerts 2021).…”
Section: Introductionmentioning
confidence: 99%